A reforma curricular do curso de licenciatura em Educação Física da USP (2004/2006): posições e tomadas de posição no campo universitário - Ronaldo Castro D Avila (2014)
Teacher preparation programs in Physical Education, thanks to the need of their curriculum reformulation and with the objective of adequacy to the resolutions CNE/CP Nº 01 and CNE/CES Nº 07, have developed specific pedagogical proposals in order to answer to the new educational demands in this field. Thus, we discuss in this research the curriculum reform process of a teacher preparation program in Physical Education of an important Brazilian public university São Paulo University (USP) , between 2004 and 2006, through the analysis of documents and dialogues with agents and groups of agents who were protagonists in this reform. This academic investigation is inserted in the panel of researches on undergraduate programs in Physical Education which have the teacher education as object of study. In this way, this research aims at analyzing the curriculum reform process of an undergraduate program in Physical Education and its consequences to the implementation or no implementation of changes in the curriculum of the teacher education program at USP. During the development of this study, we have used Bourdieus concept of field as theoretical foundation to understand the dynamic of the competitive struggles within the Physical Education sub field and its influence in the curriculum reform process of the teacher education program. We have also used the concepts of capital and habitus triad that constitutes the central aspects of Bourdieus work (BOURDIEU, 1983; 1984; 1992; 2003; 2007a; 2007b). In order to achieve the research objectives, it was developed a case study and a qualitative methodological approach. We have used as data collecting instruments documentary analysis, in order get more information about the institution history and the curriculum reform of the teacher preparation program, and also the semi-structured interview with the agents involved in this reform process identified in the exploratory phase of the research. The collected data were able to reveal how the curricular reform of this teacher education program took place and how the power positions of the sub field were distributed, relating these relations to their influence grade on the definition of the curriculum configuration. It was possible to identify agents and groups of agents, their interests and strategies adopted to either the transformation or preservation of the preexisting curriculum.